The Longed-For Voice: A Paralinguistic Suprasegmental Study of the Female Character in the Series Gadis Kretek - Rahmawati, Anisa Asih; Ilmi , Aulia Fadzilatul; Zahro, Fatimatuz; Shofah, Novia Adibatus (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Gadis Kretek (Cigarette Girl) series, adapted from Ratih Kumala’s novel, reconstructs the dynamics of the kretek (clove cigarette) industry in the 1960s while presenting a complex representation of women within a patriarchal social structure. This study aims to analyze suprasegmental paralinguistic features in the speech of female characters to uncover practices of resistance against masculine dominance. The analysis combines a suprasegmental paralinguistic approach focusing on intonation, stress, and pauses with feminist literary criticism as the conceptual framework for interpreting female voice as a form of symbolic resistance. Data were collected through documentation and transcription of the series’ dialogues, with a focus on utterances reflecting specific ideological intentions. The findings indicate that prosodic elements do not merely convey emotion but also reflect the social position and agency of women within the narrative. The character Dasiyah emerges as a representation of a woman who challenges patriarchal structures through vocal articulation that is strong, stable, and emphatically delivered. This study demonstrates that paralinguistic features can serve as a critical medium for interpreting gender discourse in audiovisual texts.